Trends in Staging, Treatment, and Survival in Colorectal Cancer Between 1990 and 2014 in the Rotterdam Study - Lavrijssen, Birgit D. A.; Ruiter, Rikje; Fest, Jesse; Ikram, Mohammad A.; Stricker, Bruno H.; van Eijck, Casper H. J. (Frontiers in Oncology, 2022)
Background: This study aims to assess trends in patient-related factors and treatment strategies in Dutch colorectal cancer (CRC) patients and their effect on survival. Methods: Data were obtained from the Rotterdam study; an ongoing population-based study of individuals aged ≥45 years. Between 1990 and 2014, incident, pathology-confirmed CRC cases were divided into two groups based on date of diagnosis (either before or after January 1st 2003). Patient characteristics, initial treatment and date of mortality were collected. Analyses were performed using Kaplan-Meier and Cox Proportional hazard models. Results: Of 14,928 individuals, 272 developed colon cancer and 124 rectal cancer. Median follow-up was 13.2 years. Patients diagnosed after January 1st 2003 were treated chemotherapeutically more often than those diagnosed prior to this date in colon cancer (28.6% vs. 9.1%, p=0.02) and treated more often with chemotherapy (38.6% vs. 12.3%, p=0.02) and radiotherapy (41.3% vs. 10.2%, p=0.001) in rectal cancer. Overall survival, adjusted for patient-, tumor characteristics and treatment, improved in rectal cancer (HR 0.31, 95% CI 0.13-0.74), but remained stable in colon cancer (HR 1.28, 95% CI 0.84-1.95). Conclusion: Chemotherapeutic agents and radiotherapy are increasingly used in CRC patients. Survival in rectal cancer improved, whereas in colon cancer this was not observed.